Historical identity and cultural difference: a critical note - Dube, Saurabh (2002)
Questions of identity and difference have often been articulated within two broad strands of scholarship. One that stresses transnational processes and overlapping histories and the other that looks to the fragmentary and everyday processes in the past and the present, emphasising critical difference over historical identity. This paper explores two critical events of current history; two seemingly disparate cases that show persistent affunities - the opening ceremony of the Sydney Games in 2000 and the destruction of the Bamiyan Buddhas early this year - as a starting point in thinking through discrete academic orientations toward identity and difference. - Reproduced.
Keywords: Cultural identity